On gauge consistency in gauge-fixed Yang-Mills theory - Pawlowski, Jan M.; Schneider, Coralie Sophie; Wink, Nicolas (Arxiv, 2022)
We investigate BRST invariance in Landau gauge Yang-Mills theory with functional methods. To that end, we solve the coupled systems of functional renormalisation group for the momentumdependent ghost and gluon propagator, ghost-gluon, and three- and four-gluon vertex dressings. The equations for both, transverse and longitudinal correlation functions are solved self-consistently: all correlation functions are fed back into the loops. Additionally, we also use the Slavnov-Taylor identities for computing the longitudinal correlation functions on the basis of the above results. Then, the gauge consistency of the solutions is checked by comparing the respective longitudinal correlation functions. We find good agreement of these results, hinting at the gauge consistency of our setup.